Toxorhynchites (Lynchiella) caatingensis sp. nov. (Diptera: Culicidae) from the semi-arid region of Brazil - Andrade, David Campos; Corte, Roseli La (Zootaxa, 2021)
This publication describes a new species of mosquito of the genus Toxorhynchites Theobald, 1901, subgenus Lynchiella Lahille, 1904. The species was found during an exploratory survey of the Culicidae in the Caatinga biome, which is unique to Brazil and characterized by a semi-arid climate. Because of the specific characteristics of the biome, it has potential for endemism of species that have adapted to its restrictive conditions, particularly those imposed by severe drought. The new species, Toxorhynchites (Lynchiella) caatingensis, is a phytotelmic species that inhabits bromeliads and has an unknown biology. It belongs to a species complex that is hereafter referred to as the Violaceus Complex, which comprises three species that are found in the same type of habitat and have similar morphology: Tx. caatingensis n. sp., Tx. mariae (Bourroul, 1904) and Tx. violaceus (Wiedemann, 1820). We describe the larva, pupa, adult female and male genitalia of specimens collected as larvae from the tank bromeliad Aechmea aquilega (Salisb.) Griseb. The main distinctive characteristics of the species are the presence of three lateral tufts on the terminal abdominal segments (one pale and the others dark); a blue midline on the abdominal sterna; in the pupa, the pentagonal shape of the paddle and the length of seta 6-V. PCR reactions were carried out for the mitochondrial CO1 gene fragment, which placed the new species in the subgenus Lynchiella. No match was found with any species recorded in GenBank. The subgenus now includes 17 species.